Distribution of information through the social media / Nur Syahira Zaidi Rasmadi - Zaidi Rasmadi, Nur Syahira (Faculty of Information Management, 2015)
Social Media is the platform to spread the information today. Information can be define as data that right and also timely, something that we can tell to other based on the source that we got whether it is printed or non-printed. It also specific and organized for a purposed and presented within a context that give it a meaning and relevance and also can lead to an increase in understanding and decrease in uncertainly.